“Culture Is So Interspersed”: Child-Minders’ and Health Workers’ Perceptions of Childhood Obesity in South Africa - Roger Figueroa; Jaclyn Saltzman; Jessica Jarick Metcalfe; Angela Wiley (Journal of Obesity)
Introduction. Forty-one million children globally are overweight or obese, with most rapid rate increases among low- and middle-income nations. Child-minders and health workers play a crucial role in obesity prevention efforts, but their perceptions of childhood obesity in low- and middle-income countries are poorly understood. This study aims to (1) explore child-minders and health workers’ perceptions of the causes, consequences, potential strategies, and barriers for childhood obesity prevention and intervention in Cape Town, South Africa and (2) to provisionally test the fit of a socioecological framework to explain these perceptions. Methods. Twenty-one interviews were recorded, transcribed, and analyzed through analytic induction. Results. Participants identified multilevel factors and contexts, as well as potential consequences and priorities of interest in addressing childhood obesity. An adapted childhood obesity perceptions model was generated, which introduces an overarching cultural dimension embedded across levels of the socioecological framework. Conclusions. Culture plays a pivotal role in explaining obesogenic outcomes, and the results of this study demonstrate the need for further research investigating how obesity perceptions are shaped by cultural frames (e.g., social, political, and historical). Understanding the causes, consequences, and potential interventions to address obesity through a cultural lens is critical for promoting health in low- and middle-income nations.